Diskursus Perdebatan Praktik Money Politic dalam Perspektif Metode Istishlahy - Rafiq, Mahbub Ainur (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This article aims to explain the debate about money politics from an istishlahy perspektif. Money politics is an effort to influence the electoral masses in exchange for certain materials that someone does not exercise their right to vote or exercise their rights in a certain way. This practice make the stability of the political climate is disrupted. That is why, positive law prohibits the practice of money politics. The discourse on money politics is very interesting in the fiqh literature, if there is a concern that not giving money in a contestation of positions will fall to the wrongdoer. So the majority of scholars give privileges to do this practice, and this is not included in the category of bribery. The researcher is interested in examining more deeply the discourse on the debate about the provisions of the practice of money politics. This qualitative research using the ushul fiqh approach aims to examine methodologically more deeply the discourse on the debate about the provisions of the practice of money politics.This debate will be examined using the istishlahy method. The result of this article is: First, this practice can be applied to risywah. Due to the similarity ‘illat (logical ratio), namely khauf al-mail. Second, there is a privilege in conditions that are very far from idealism in practicing money politics, as long as the indicators which are the prevailing factors of money politics practice are found in the socio-political reality.